A Cross-Sectional Study of Empathy and Emotion Management: Key to a Work Environment for Humanized Care in Nursing - Pérez-Fuentes, María del Carmen; Herrera-Peco, Ivan; Molero Jurado, María del Mar; Oropesa Ruiz, Nieves Fátima; Ayuso-Murillo, Diego; Gázquez Linares, José Jesús (Frontiers in Psychology, 2020)
Introduction: At the present time, technological advances have increased technification of healthcare services, in which high priority is given efficiency and results achieved, leading healthcare personnel to prioritize administrative and procedural aspects to the detriment of humanization of care and the work environment. Objective: This study was intended to continue progress in research in the work environment based on the humanization construct by analyzing the explanatory value of emotional intelligence and empathy in nursing personnel. Method: The study was quantitative, observational and cross-sectional. The sample was made up of 338 Spanish nurses with a mean age of 32.20 (SD=7.54; range 22-56). The instruments employed for analysis were the Healthcare Professional Humanization Scale, Brief Emotional Intelligence Inventory for Adults and Basic Empathy Scale. Results: Mood and stress management, both emotional intelligence components, and cognitive empathy, explained over half (51%) of the variability found in humanization of care in a sample of nurses. Furthermore, the mediation models proposed emphasized the mediating role of cognitive empathy in stress management and improvement in mood and its relationship to humanization. Conclusion: It is recommended that healthcare professionals reinforce their personal competencies in order to attend to the needs of their patients empathetically, and improve emotional competencies for coping successfully with potentially stressful situations.